CRISPR/Cas9-Mediated in vivo Genetic Correction in a Mouse Model of Hemophilia A - Luo, Sanchuan; Li, Zhongxiang; Dai, Xin; Zhang, Rui; Liang, Zhibing; Li, Wenzhou; Zeng, Ming; Su, Jinfeng; Wang, Jun; Liang, Xia; Wu, Yong; Liang, Desheng (Frontiers in Cell and Developmental Biology, 2021)
Hemophilia A (HA), a common bleeding disorder caused by a deficiency of coagulation factor VIII (FVIII), has long been considered an attractive target for gene therapy studies. However, full-length F8 cDNA cannot be packaged efficiently by adeno-associated virus (AAV) vectors. As the second most prevalent mutation causing severe HA, F8 intron 1 inversion (Inv1) is caused by an intrachromosomal recombination, leaving the majority of F8 (exons 2-26) untranscribed. In theory, the truncated gene could be rescued by integrating a promoter and the coding sequence of exon 1. To test this strategy in vivo, we generated an HA mouse model by deleting the promoter region and exon 1 of F8. Donor DNA and CRISPR/SaCas9 were packaged into AAV vectors and injected into HA mice intravenously. After treatment, F8 expression was restored and activated partial thromboplastin time (aPTT) was shortened. We also compared two liver-specific promoters and two types of integrating donor vectors. When an active promoter was used, all of the treated mice survived the tail-clip challenge. This is the first report of an in vivo gene repair strategy with the potential to treat a recurrent mutation in HA patients.